Geothermy and its Future in Indonesia - M.T. Zen (Journal of Mathematical and Fundamental Sciences, 1973)
Abstract. The basic concept of a commercial steamfield is discussed and defined in this paper. Based on this discussion potential areas are indicated in a map. It is found that not less 24 geotherrnal areas are prospectable. However, it is found that very little is known about the exact potential of Indonesia in the field of geothermy. Anticipating the rising demand in electricity within the context of the broader industrialisation program of Indonesia and the limitation of its fossil fuel reserve, it is suggested that all possibilities for utilising different kinds of energy, including geothermy should be explored as far as possible. Ringkasan. Konsep dasar dari suatu medan uap alam komersil diperbincangkan dan didefinisikan. Berdasarkan pada diskusi tersebut daerah-derah dengan potensi geothermy dicantumkan ke dalam peta. Ternyata bahwa tak kurang dari 24 medan hyperthermal tersebar di seluruh wilayah Indonesia yang berkemungkinan untuk dapat dieksplorasikan lebih lanjut. Saying sekali bahwa sangat sedikit yang diketahui mengenai potensi Indonesia sesuangguhnya dalam bidang ini. Menghadapi permintaan tenaga listrik yang semakin menanjak dalam rangka pengembangan program industrialisasi Indonesia, dan terbatasnya persediaan bahan bakar fossil, pengarang menganjurkan agar semua segi dan kemungkinan pemanfaatan segala macam sumber energi , termasuk geothermy, dijajaki sejauh mungkin.